The organized chaos of Egberto Gismonti in Frevo: improvisation and thematic development (Per Musi, 2013)
Analytical study about the compositional and improvisational practices of Egberto Gismonti in his music Frevo for piano, especially in the intersection between the procedures of thematic development and improvisation. Departing from the audio track included in the Alma album (GISMONTI, 1987a), which transcription was realized by the authors of the present article and published in the present volume of Per Musi (GISMONTI, 2013, pp.125-144), it reveals how Gismonti achieves great coherence in the realization of Frevo by resorting to the recurrence and varied transformation of only five motives throughout the work. The analysis also reveals a hybridization of elements from popular music (the Brazilian frevo, jazz, improvisation) and classical music (reflecting piano technique methods, J. S. Bach, F. Chopin, H. Villa-Lobos, the First and Second Vienna Schools and the post-1950 period).